2016
DOI: 10.1038/ncomms12333
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrogenation of anhydrous methanol at room temperature by o-aminophenol-based photocatalysts

Abstract: Dehydrogenation of anhydrous methanol is of great importance, given its ubiquity as an intermediate for the production of a large number of industrial chemicals. Since dehydrogenation of methanol is an endothermic reaction, heterogeneous or homogeneous precious-metal-based catalysts and high temperatures are usually required for this reaction to proceed. Here we report the photochemical dehydrogenation of anhydrous methanol at room temperature catalysed by o-aminophenol (apH2), o-aminophenolate (apH−) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 70 publications
(128 reference statements)
0
15
0
Order By: Relevance
“…On the other hand, we found that the new signals emerged at 0.88, 0.89, and 1.19 ppm in the 1 H NMR spectrum of a THF- d 8 solution of t -Bu 2 S 2 after photo-irradiation ( λ ex = 300 ± 10 nm), which demonstrates the photoreactivity of t -Bu 2 S 2 (Fig. 4c ) 63 . These resonances are thus indicative of the in-situ formation of t -Bu 2 S 2 .…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…On the other hand, we found that the new signals emerged at 0.88, 0.89, and 1.19 ppm in the 1 H NMR spectrum of a THF- d 8 solution of t -Bu 2 S 2 after photo-irradiation ( λ ex = 300 ± 10 nm), which demonstrates the photoreactivity of t -Bu 2 S 2 (Fig. 4c ) 63 . These resonances are thus indicative of the in-situ formation of t -Bu 2 S 2 .…”
Section: Resultsmentioning
confidence: 79%
“…Subsequently, we attempted to identify the active species by trapping experiments. It was previously reported that 2-methylpropane-2-thiol ( t -BuSH) can act as a hydrogen (H) radical scavenger forming di- tert -butyl disulfide ( t -Bu 2 S 2 ) 63 , 64 . The detection of t -Bu 2 S 2 among the photochemical reaction products of opda and 1 revealed the H radical generation during the reaction ( vide infra ).…”
Section: Resultsmentioning
confidence: 99%
“…11 Beller and other researchers also highlighted the role of waterpromoted dehydrogenation of formaldehyde to formic acid and H 2 during the methanol dehydrogenation reaction. 25,38 Notably, Lin et al also reported efficient hydrogen production from methanol over Pt/α-MoC with a higher water content (CH 3 OH/H 2 O molar ratio of 1 : 3 and 1 : 1). 35 Notably, we found that the base played a crucial role in generating the active Ru nanoparticles in the initial hour of the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Another Fe photocatalyst was applied by Chang and co-workers in which the metal complex trans -[Fe II (apH) 2 (MeOH) 2 ] (apH = o -aminophenolato ligand) ( 89 ) was able to promote anhydrous methanol dehydrogenation at room temperature without the need for additional photosensitizers . Mechanistic studies suggested that hydrogen radicals induced by photocatalysis trigger this hydrogen evolution reaction.…”
Section: Methanol As a Hydrogen Storage Mediummentioning
confidence: 99%